Perancangan Sistem Udara Bertekanan Untuk Cabin Pressurization dan Praktikum Mahasiswa - Febrian Setiaji; Teguh Wibowo (INOVTEK - SERI MESIN, 2021)
The compressed air system is also called a vital system because it functions as a provider of compressed air for activities such as lifting and holding, turning and pressing, and even can be used for cleaning. In addition to those activities, it can also be used as a supply to the cabin pressurization simulation tool so that the pressure in the cabin can match the pressure of the aircraft when it is on the ground.This final project entitled "Design of a Compressed Air System for Cabin Pressurization and Student Practices" designed a compressed air system that will be used to simulate cabin pressurization by examining the appropriate components and calculating pressure losses in the system. The results of the preparation of this final project are expected to be useful to help provide an overview of the compressed air system and the manufacture of a pressurized air distribution system in Polban Aeronautical Engineering hangar.                                                                                                       Keywords: System, distribution, compressed air, pipes, cabin pressurization